John Noble report - Noble, John, active 1880.
Survey report on land owned by Noble in Chicago on Lake Michigan.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Michigan, Lake; Real property -- Illinois -- Chicago; Chicago (Ill.) -- Surveys